Principles of Data Management - Facilitating Information Sharing (3rd Edition) - Gordon, Keith (BCS The Chartered Institute for IT, 2022)
Data is a valuable corporate asset and its effective management is vital to an organisation's success. This professional guide covers all the key areas of data management, including database development and corporate data modelling. It is business-focused, providing the knowledge and techniques required to successfully implement the data management function. This new edition adds chapters on linked data, concept systems and big data and artificial intelligence.